When is the use of L1 (Portuguese) appropriate in groups of adolescents in monolingual L2 (English) classes? A teacher-training proposal - de Lima, Rosangela Nunes (Revista Leitura, 2019)
Many non-native teachers of English as a Foreign Language seem to feel guilty about using L1 in the classroom, especially with teenagers. This work explores the need to use the adolescents' native language. It looks at theoretical aspects, authentic opportunities and contexts for teachers to feed in or teach the kind of language necessary for real communication. DOI: 10.28998/0103-6858.2007v1n39p93-110